PERRY, David. Spirit Baptism: The Pentecostal Experience in Theological Focus. (17th April 2019) - Chike, Chigor
Abstract : PERRY, David. Spirit Baptism: The Pentecostal Experience in Theological Focus. Leiden: Brill, 2017. 276pp. ISBN: 9789004335929. £33.91.